Patient surface and isocenter dose in FLUORO-CT. (September 2016) - Pereira, J.; Pereira, M.F.; Sarmento, S.; Oliveira, A.D.; Alves, J.G.; Sousa, M.J.; Cunha, L.; Dias, A.G.; Mendes, B.; Cardoso, J.V.; Santos, L.M.; Gouvêa, M.; et al.
Abstract : Introduction: In CT exams the quantities used to estimate the dose, for example, the CTDI, the CTDI vol and the DLP, are related with isocenter and peripheral phantom measurements. However, during fluoro-CT (CTF) scans executed in the IPOPFG a set of dose profile measurements lead to the conclusion that the patient skin surface dose can be an important dose parameter usually not considered. Purpose: The aim of this work was to perform measurements of dose profiles at the isocenter of the gantry and at the surface of patients undergoing CTF procedures allowing comparison of the dose levels. Materials and methods: The measurements were performed using a Gafchromic XRQA film (International Speciality Products, Wayne, NJ, USA) and a 4-slice Toshiba Asteion CT-scanner, operated with 8-mm beam collimation and 0.75 s rotation time. Results: Several dose profiles were obtained free-in-air at the isocenter and at patient surface. Due to the specificities of the CFT practice it was found that in the body region exposed to radiation the dose level can reach rather high values, not described by the CTDI or DLP quantities which are referenced to the isocenter dose levels. Conclusion: The comparison between isocenter and surface dose profiles pointed out the need to revise the CTDI concept in order to consider patient skin dose which is, in general, positioned out of the axis of rotation of the X-ray tube rotation.